2007
DOI: 10.1021/jp066511a
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Amphiphile Self-Assembly Phases in Protic Ionic Liquids

Abstract: A range of protic ionic liquids (PILs) have been identified as being capable of supporting the self-assembly of the nonionic surfactants myverol 18-99 K (predominantly monoolein) and phytantriol. PIL-surfactant penetration scans have provided a high throughput technique to determine which lyotropic liquid crystalline phases were formed in the 40 PIL-surfactant systems investigated. Lamellar, inverse hexagonal, and bicontinuous cubic phases that are stable in excess PIL have been observed in surfactant-PIL syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
169
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(174 citation statements)
references
References 30 publications
5
169
0
Order By: Relevance
“…At almost the same time, the aggregation behavior of Brij 35, Brij 700, Tween 20, and Triton X-100 has been investigated within lowviscosity emim-Tf 2 N by Fletcher and Pandey [9]. Greaves et al observed the lyotropic liquid crystal phases that are stable in excess protic ionic liquid (PIL) in surfactant-PIL systems [10]. The group of Lodge demonstrated the flexibility of amphiphilic PB-PEO block copolymers for controlling micellar structures (spherical micelle, wormlike micelle, and bilayered vesicle) in bmim-PF 6 [11].…”
Section: Introductionmentioning
confidence: 99%
“…At almost the same time, the aggregation behavior of Brij 35, Brij 700, Tween 20, and Triton X-100 has been investigated within lowviscosity emim-Tf 2 N by Fletcher and Pandey [9]. Greaves et al observed the lyotropic liquid crystal phases that are stable in excess protic ionic liquid (PIL) in surfactant-PIL systems [10]. The group of Lodge demonstrated the flexibility of amphiphilic PB-PEO block copolymers for controlling micellar structures (spherical micelle, wormlike micelle, and bilayered vesicle) in bmim-PF 6 [11].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of high throughout surfactant-PIL penetration scans, they found that lamellar, inverse hexagonal, and bicontinuous cubic phases can exist as thermodynamically stable phases in excess PIL in select surfactant-PIL systems. Changes to the cation and anion can be used to modify the liquid crystalline phases [61]. They also discovered that PILs can mediate solvent hydrocarbon interactions and promote amphiphile self-assembly.…”
Section: Self-assemblied Liquid Crystals In Ilsmentioning
confidence: 99%
“…In the last three or four years, PILs containing primary, secondary, and tertiary ammonium cations have been extensively investigated by Drummond et al [17,[60][61][62] . The presence of hydroxy groups on PILs leads to higher surface tensions and consequently higher values of the Gordon parameters (the Gordon parameters are generally regarded as measures of cohesiveness of liquids and indications of the driving forces for self-assembly of amphiphiles).…”
Section: "Protic" Ionic Liquids On Nitrogenmentioning
confidence: 99%
“…The proton availability characteristic of these salts is considered the main factor responsible for their smaller potential windows (normally lower than 3 V) relative to aprotic ILs and their greater sensitivity to the nature of electrode materials. [60][61][62][63][64][65][66][67][68] Other bases have also been employed to prepare PILs in the last five years; many protonated pyridinium-and imidazolium-based ILs have been synthesized and applied in synthesis (see below).…”
Section: N][hcoo]mentioning
confidence: 99%
See 1 more Smart Citation